The Radiation-Induced Regenerative Response of Adult Tissue-Specific Stem Cells: Models and Signaling Pathways - Serrano Martinez, Paola (Cancers (Basel), 2021)
SIMPLE SUMMARY: A common side effect of radiotherapy is the impairment of integrity and functionality of the co-irradiated surrounding normal tissue. Homeostasis and regeneration of many organs are maintained by specific stem/progenitor cells. Radiation can harm these resident stem/progenitor populations involving the disruption of the signaling cascade of pathways known to normally sustain stem/progenitor cellular activity. This review describes the currently existing models used to study the response of stem/progenitor cells to irradiation and the key signaling pathways involved during solid tissue-specific stem/progenitor driven regeneration. ABSTRACT: Radiotherapy is involved in the treatment of many cancers, but damage induced to the surrounding normal tissue is often inevitable. Evidence suggests that the maintenance of homeostasis and regeneration of the normal tissue is driven by specific adult tissue stem/progenitor cells. These tasks involve the input from several signaling pathways. Irradiation also targets these stem/progenitor cells, triggering a cellular response aimed at achieving tissue regeneration. Here we discuss the currently used in vitro and in vivo models and the involved specific tissue stem/progenitor cell signaling pathways to study the response to irradiation. The combination of the use of complex in vitro models that offer high in vivo resemblance and lineage tracing models, which address organ complexity constitute potential tools for the study of the stem/progenitor cellular response post-irradiation. The Notch, Wnt, Hippo, Hedgehog, and autophagy signaling pathways have been found as crucial for driving stem/progenitor radiation-induced tissue regeneration. We review how these signaling pathways drive the response of solid tissue-specific stem/progenitor cells to radiotherapy and the used models to address this.